Association between the C-reactive protein-albumin-lymphocyte (CALLY) index and mortality in elderly patients with dysphagia requiring nutritional support - Shen, Hui; Jin, Tonghu; Mei, Qing; Guan, Hao; Yan, Kuang; Liu, Aihua (Frontiers in Neurology, 2025)
BackgroundWhile the novel C-reactive protein-albumin-lymphocyte (CALLY) index—integrating inflammatory, nutritional, and immune markers—has proven valuable for prognosis in various diseases, its utility in predicting outcomes for dysphagia patients is still unclear.MethodsThis retrospective cohort analysis utilized data sourced from the Dryad Digital Repository. The CALLY index (albumin × lymphocyte count/C-reactive protein × 104) was calculated. After logarithmic transformation (Ln-CALLY), the patients were divided into low Ln-CALLY group (≤ 2.21) and high Ln-CALLY group (>2.21). All-cause mortality served as the primary endpoint. The association between Ln-CALLY and outcomes was evaluated using Kaplan-Meier analysis with log-rank testing and multivariable Cox proportional hazards regression. The dose-response relationship was evaluated by restricted cubic splines (RCS).ResultsThis study enrolled 253 elderly dysphagia patients. Analysis revealed Ln-CALLY as a significant predictor of all-cause mortality.ConclusionThe CALLY index shows promise as a predictor of mortality risk and long-term outcomes in older dysphagia patients.